Hofmeister effect-assisted chain bundling and limited coalescence in Pickering emulsion to construct tough and conductive scaffolds for bone regeneration - Huan Tan; Linlong Li; Xue Bai; Yu Deng; Shichen Hu; Yuanyuan Zhou; Shirun Chu; Zili Guo; Jiahao Zhang; Hua Li; Jie Weng (Chemical Engineering Journal, 2025)

Mechanisms of ammonia-like off-flavors formation in dried shrimp: Contribution of spoilage microbiota and their metabolism - Yan Bai; Min Wang; Xiaoyan Zhang; Zhigang Ke; Shichen Zhu; Yuting Ding; Xuxia Zhou (Food Chemistry, 2025)

Tianwen-1 and MAVEN observations of Martian oxygen ion plumes - Xiao Ma; Anmin Tian; Ruilong Guo; Lihui Chai; Quanqi Shi; Shichen Bai; Qiugang Zong; Linggao Kong; Wenya Li; Binbin Tang; Aibing Zhang; Suiyan Fu; et al. (Icarus, 2023)

Automated machine learning-based models for predicting and evaluating antibiotic removal in constructed wetlands - Hongxu Bao; Wanxin Yin; Hongcheng Wang; Yin Lu; Shijie Jiang; Fidelis Odedishemi Ajibade; Qinghua Ouyang; Yongji Wang; Shichen Nie; Yu Bai; Huiliang Gao; Aijie Wang (Bioresource Technology, 2023)

Localization of QTL for cold tolerance at the germination stage of rice (Oryza sativa L.) using recombinant inbred lines - Liangzi Cao; Shukun Jiang; Guohua Ding; Tongtong Wang; Liangming Bai; Jinsong Zhou; Yu Luo; Tianshu Xia; Hui Jiang; Kai Liu; Xueyang Wang; Guang Yang; et al. (Genetic Resources and Crop Evolution, 2022)
The cold tolerance of germinating direct-sown rice ( Oryza sativa L.) has an increased rate of emergence, which ensures vigorous seedling growth. Research on QTL localization for cold tolerance at the germination stage can assist in molecular marker-assisted selection and enhance breeding efficiency. In this study, 94 populations of recombinant self-incompatible lines from Heigu and Ha 9366 were selected to investigate germination rates at low temperatures. It was found that two QTL loci (qLTG-3 and qLTG-12) were located at different germination times on chromosomes 3 and 12, respectively. The two QTLs at three different germination times, located using QTL, accounted for 21.3–25.9% of the phenotypic variation. Moreover, a reciprocal effect was detected between the two QTLs. The double QTLs increased the germination rate by 22–27% in this population. Additionally, qLTG-12 improved cold tolerance at the seedling stage. The results of this study might provide the materials and molecular markers for future molecular marker-assisted breeding for cold tolerance at the germination stage.

Identification of candidate genes for panicle length in Oryza sativa L. ssp. japonica via genome-wide association study and linkage mapping - Hongliang Zheng; Shichen Sun; Liangming Bai; Shukun Jiang; Guohua Ding; Tongtong Wang; Hongwei Zhao; Jingguo Wang; Hualong Liu; Luomiao Yang; Yan Jia; Xin Wei; et al. (Euphytica, 2022)

Protective effects of grape seed extract fractions with different degrees of polymerisation on blood glucose, lipids and hepatic oxidative stress in diabetic rats - Zhaoxia Wu; Siyao Shen; Jiaqian Jiang; Dehong Tan; Donghua Jiang; Bing Bai; Xiyun Sun; Shichen Fu (Natural Product Research, 2015)